AB0032 ABNORMAL STATUSES OF PERIPHERAL CD4+T CELL SUBSETS IN PATIENTS WITH GOUT AND THEIR CHANGES AFTER RECEIVING COMBINED IMMUNOMODULATORY THERAPY. (2nd June 2020) - Chang, M. J.; Zhang, S. X.; Zhao, L.; Qiao, J.; Zhang, J.; Qiu, M. T.; Zhao, R.; Li, Y.; Wang, C.; Luo, J.; Liu, G. Y.; Gao, C.; et al.
Abstract : Background: Gout is a chronic systemic inflammatory disease that results from the deposition of monosodium urate crystals in joints and the associated activation of the innate immune system associated with hyperuricemia 1 . As the pathogenesis of gout is still a matter of speculation and debate, accumulating evidence converges on inflammasome activation and immunological dysregulation 2 . However, the detailed statuses of lymphocyte subsets in patients with gout are unknown and influence of immunomodulatory combination therapies on the lymphocyte subsets remain to be clearly evaluate 3 . Objectives: To evaluate the quantitative statuses of peripheral CD4 + T subpopulations in patients with gout and further investigate the effects of immunomodulatory combination therapies on those cells. Methods: Total 247 patients who met the clinical criteria of gout from the American College of Rheumatology and 206 healthy controls (HCs) were enrolled in this retrospective cross-sectional study. Among those patients, 70 follow-up patients donated their peripheral blood after receiving immunomodulatory drugs (e.g., low-dose interleukin-2, rapamycin, metformin, retinoic acid, etc). The absolute numbers of Th1, Th2, Th17 and Tregs in peripheral CD4 + T subsets were detected by flow cytometry combined with standard absolute counting beads. Results: Compared with HCs, the absolute numbers of Th1 and Th17 were evidently increased in gout patients ( P <0.001), while the level of Tregs was significantly decreased ( P <0.05) (Figure 1 ). After immunomodulatory combination treatments, there were dramatical increases in a wide variety of CD4 + T subsets such as Th1, Th17 and Tregs ( P <0.05). Interestingly, the increased amount of Tregs was much more than that of other Teffs, leading to the decrease ratios of Teffs/Tregs such as Th2/Tregs, restoring immune homeostasis (Figure 2 ). Conclusion: This cross-sectional study clarified the abnormal statuses of CD4 + T subsets in gout patients, suggesting that CD4+T subsets, especially Tregs, might be relevant and play a crucial role in the pathogenesis of gout, thus providing a potential therapeutic target for gout patients. Immunomodulatory combination therapies effectively increase the number of Tregs and may help for gout patients' symptom remission. References: [1]Ramsubeik K, Ramrattan LA, Kaeley GS, et al. Effectiveness of healthcare educational and behavioral interventions to improve gout outcomes: a systematic review and meta-analysis. Therapeutic advances in musculoskeletal disease 2018;10(12):235-52. doi: 10.1177/1759720x18807117 [published Online First: 2018/12/06] [2]Stiburkova B, Pavelcova K, Pavlikova M, et al. The impact of dysfunctional variants of ABCG2 on hyperuricemia and gout in pediatric-onset patients. Arthritis Res Ther 2019;21(1):77. doi: 10.1186/s13075-019-1860-8 [published Online First: 2019/03/22] [3]Raucci F, Iqbal AJ, Saviano A, et al. In-depth immunophenotyping data relating to IL-17Ab modulation of circulating Treg/Th17 cells and of in situ infiltrated inflammatory monocytes in the onset of gouty inflammation. Data Brief 2019;25:104381. doi: 10.1016/j.dib.2019.104381 [published Online First: 2019/09/07] Acknowledgments: None. Disclosure of Interests: None declared